2019
DOI: 10.31083/j.rcm.2019.02.510
|View full text |Cite
|
Sign up to set email alerts
|

Persistent left superior vena cava identified by transesophageal echocardiography

Abstract: A 70-year-old female with severe aortic stenosis presented for aortic valve replacement and underwent routine preoperative Swan-Ganz catheter placement. Transesophageal echocardiography demonstrated a dilated coronary sinus with a catheter present. A high suspicion of venous anomaly prompted an agitated saline study. Flow through the coronary sinus into the right atrium was observed, confirming the presence of a persistent left superior vena cava. Although the persistent left superior vena cava has a low preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Some studies have concluded that transesophageal echocardiography (TEE) with agitated saline plays a significant role in diagnosis and can be the imaging tool of choice when evaluating PLSVC. 5,6 When PLSVCs are suspected with a dilated CS due to volume overload, 7 it is paramount that trained staff administer agitated saline via the left arm, and not the right, when the opportunity persists. In a PLSVC, bubbles will first appear in the CS before filling the right heart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have concluded that transesophageal echocardiography (TEE) with agitated saline plays a significant role in diagnosis and can be the imaging tool of choice when evaluating PLSVC. 5,6 When PLSVCs are suspected with a dilated CS due to volume overload, 7 it is paramount that trained staff administer agitated saline via the left arm, and not the right, when the opportunity persists. In a PLSVC, bubbles will first appear in the CS before filling the right heart.…”
Section: Discussionmentioning
confidence: 99%
“…13 The hemodynamic implications of this anomaly are typically minimal; however, these incidental findings are important to forward to interventionists as their presence may make some procedures challenging to perform. 5,[14][15][16] One challenging intervention in the presence of a PLSVC is pacemaker implantation. 17 A case study by Totorean et al reports on an unknown PLSVC at the time of lead implantation, which deemed traditional transvenous implantation not feasible.…”
Section: Discussionmentioning
confidence: 99%
“…PLSVC is caused by abnormal degeneration of the left anterior main vein, which starts in front of the left jugular vein and the left pulmonary artery, and in the lateral edge of the left atrium. It converges into the CS through the left atrioventricular sulcus, and finally enters the right atrium[ 10 ]. Based on the location of the flow into the heart, PLSVC is often divided into four types.…”
Section: Discussionmentioning
confidence: 99%
“…The only limitation of thoracic contrast computed tomography is radiation exposure. MRI could be a best alternative significantly superior to both transthoracic and transesophageal echocardiography [ 9 , 10 ]. In our case, symptoms suggest the diagnosis of asthma.…”
Section: Discussionmentioning
confidence: 99%